Guidelines for Accessibility: ensuring the usability of mobile applications for visually impaired users - Siebra, Clauirton; Correia, Walter; Penha, Marcelo; Macêdo, Jefté; Quintino, Jonysberg; Anjos, Marcelo; Florentin, Fabiana; Q. B. Silva, Fabio; L M Santos, Andre (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2018)
Our current project involves the use of a multistage research method to specify a guideline for mobile applications, which intends to support visually impaired users. This paper discusses the employment of this guideline along the development of a mobile application for personal financial management. Such application was evaluated by a group of visually impaired volunteers and the evaluation results were used as a source of insights to refine the guideline and its requirements. Qualitative interviews show that the guideline ensures a higher level of usability when compared to previous experiences of volunteers with other applications. Thus, such outcomes confirm the guideline potential as a resource to support the development of a brand new set of accessible applications.3-Our current project involves the use of a multistage research method to specify a guideline for mobile applications, which intends to support visually impaired users. This paper discusses the employment of this guideline along the development of a mobile application for personal financial management. Such application was evaluated by a group of visually impaired volunteers and the evaluation results were used as a source of insights to refine the guideline and its requirements. Qualitative interviews show that the guideline ensures a higher level of usability when compared to previous experiences of volunteers with other applications. Thus, such outcomes confirm the guideline potential as a resource to support the development of a brand new set of accessible applications.